'Last orders'1 at the rural 'cyber pub': a failure of 'social learning'?. (1st January 2010) - McLoughlin, Ian; Preece, David
An initiative to stimulate innovation by putting rural public houses 'online' as one element of making the pub, 'the hub' of service delivery in UK rural communities is explored. Research findings are presented which show that the initiative did not develop as intended and ultimately – even in pilot form – became difficult to sustain. This abortive attempt to appropriate computer and internet technology is explained as a failure of social learning. In particular, whilst aiming with some success to assist in the configuration of the technology to the specific context and setting of the rural pub, the initiative failed to focus on developing the means and mechanisms that might have supported the development of a stronger learning culture. This could have provided the basis for the kind of social innovation required to develop and sustain a model of the rural 'cyber pub' that might then have been more widely appropriable.